Soviet-U.S. Relations. (U.S. Congressional Research., 1980)
Discusses background and issues regarding relations with the Soviet Union, including the Strategic Arms Limitation Talks, involvement in regional conflicts, human rights, and economic relations. Includes chronology, 1/14/75 to 11/9/79.